Kesesuaian Buku Teks Biologi SMA Materi Jamur Kelas X Berdasarkan Komponen Literasi Sains - Windari Ramadani; Ummi Nur Afinni Dwi Jayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the level of suitability of the fungibility material based on the aspect of scientific literacy in biology textbooks used in SMA/MA, in Bandar sub-district, Simalungun Regency. The research method used in this study is descriptive with a document analysis approach. This study focuses on analyzing aspects of scientific literacy in Fungi material in high school/MA biology textbooks in Bandar sub-district, Simalungun Regency. The results of the study showed that dimensy literacy science showed a different cell membrane. Book a has an average percentage of 78.12, while Book B has an average percentage of 92.5. In conclusion, based on the dimensions of scientific literacy, the results obtained from the analysis of scientific literacy in book A are the highest, namely science as a way of investigation, while in book B, there are two highest, namely science as a way of thinking with science and its interactions with technology and society. Keywords: Book Analysis, High School Biology, Lesson Textbooks, Dimensions of Science Literacy